2017
DOI: 10.1097/rnj.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults With Hip Arthroplasty: An Individualized Transitional Care Program

Abstract: The ITCP promoted individual physical functioning for older adults with hip arthroplasty. This study results can aid healthy transitions of elderly patients with other various diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
0
15
0
5
Order By: Relevance
“…A possible reason for the significant effect on EQ-VAS may be that a supportive environment was created through the discharge transitional care programme (Ko et al, 2019; Meleis et al, 2000), which affected subjects’ perception of health status. In this study, the discharge transitional care programme mainly focused on improving older adults’ self-care rather than providing direct intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason for the significant effect on EQ-VAS may be that a supportive environment was created through the discharge transitional care programme (Ko et al, 2019; Meleis et al, 2000), which affected subjects’ perception of health status. In this study, the discharge transitional care programme mainly focused on improving older adults’ self-care rather than providing direct intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The face-to-face intervention was conducted separately in the patient’s room by a trained nurse with approximately 4 years of experience in the orthopaedic ward. The trained nurse conducted an assessment, education and role supplementation of nursing therapeutics based on the transitional theory (Ko et al, 2019; Schumacher and Meleis, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…The transition from hospital care to outpatient care or home settings requires significant paradigm changes, which is not widely used and is mainly implemented in outpatient surgery centres or specialised orthopaedic hospitals, despite the reduction of complications and readmissions [ 41 ], with high levels of satisfaction for the person and the caregiver, as it allows for the clarification of the process and expectations [ 8 , 42 ]. There is evidence of individualised transition care programmes implemented and led by nurses that show gains in functionality in the postoperative period of hip arthroplasty [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To facilitate safe discharge transition, communication and collaboration with healthcare professionals and ensuring adequate care settings are important roles in nursing [ 17 , 34 ]. In addition, in a previous study [ 35 ], nurse-led rehabilitative practices were reported to reduce functional decline for older adults that have undergone hip fracture surgery. Thus, it is necessary for nurses to not only to recognize the importance of rehabilitative care but also establish rehabilitative strategies.…”
Section: Discussionmentioning
confidence: 99%